Zdravé bydlení v kontextu teorie zdravého města 21. století - Indrová, Gabriela (Vysoké učení technické v Brně. Fakulta stavební, 2022)
Bakalářská práce se zabývá analýzou rozvoje trendů a forem zdravého bydlení ve zdravém městě. Zabývá se také územním plánováním a analýzou vybraného zdravého města. Z nasbíraných poznatků, rozhovorů a dotazníků vychází praktická část, ve které je provedena analýza stávajících veřejných prostorů a veškerých ostatních podmínek města s cílem zhodnotit veřejný prostor a případně nabídnout možnosti pro jeho zkvalitnění. Analýza a konkrétní příklady jsou aplikovány na městě Židlochovice. Závěrečná část spojuje praktické ověření a aplikaci zjištěných aspektů zdravého města při návrhu blokové zástavby vybraného brownfieldu v městě Brně.

The bachelor thesis deals with analysis of the development of trends and forms of healthy living in a healthy city. It also deals with town and country planning and analysis of certain healthy city. The practical part comes from collected knowledge, interviews and questionnaires, in which the analysis is done of the current public spaces and all the other conditions of the city in order to evaluate the public spaces and offer opportunities for its improvement. The analysis and specific examples are applied to the town of Židlochovice. The final part combines the practical part and application of discovered aspects of a healthy city in the design of a block housing development of choosed brownfield in the city of Brno.
Healthy living in the context of the healthy city theory of the 21st century
Keywords: územní plánování; zdravé město; veřejné prostory; zdravé bydlení; udržitelná čtvrť; brownfield; dotazníkový průzkum; town and country planning; healthy city; public spaces; healthy living; healthy city; sustainable city; brownfields; questionnaire survey